ETNOMATEMATIKA PADA AKTIVITAS PASCA PANEN TEMBAKAU MASYARAKAT PENDALUNGAN DAN PENERAPANNYA SEBAGAI LEMBAR KERJA PESERTA DIDIK - Rahayu, Diah Pujining; Setiawani, Susi; Murtikusuma, Randi Pratama (Kadikma, 2018)
Ethnomatematics is a science that connects mathematics with culture in society. The purpose of this research was to describe the results of ethnomatematic exploration of post-harvest activities of tobacco farmers in the Pendalungan community and to make their products in the form of student worksheets. This type of research is qualitative with an ethnographic approach. Data collection methods used are observation and interviews. Ethnomatematics in tobacco post-harvest activities in the form of counting, measuring and designing activities. In the process of nyujen (submission) of tobacco leaves arises the mathematical concept of comparable values ​​and measurements when determining the length of the rope, determining the length of the bamboo, and determining the distance between leaves. In the process of making patterns of drying tobacco leaves, the concept of design and concept of comparable value emerged. In the fermentation process, tobacco leaves were observed in the concept of calculating when determining the length of fermentation time, and in the process of sorting tobacco leaves it was observed the concept of the ratio of turning value when determining the number of leaves per class in 1 kg. The results of the study are product teaching materials in the form of student worksheets. Student worksheets are intended for seventh grade Middle School / MTs students. This student worksheet is divided into 5 activities in the scientific approach. Keywords: Ethnomatematics, Pendalungan, Tobaccoes post-harvest